DECISION SUPPORT SYSTEM (DSS) TO DETERMINE THE INCREASE IN CUSTOMER SERVICE REPRESENTATIVE (CSR) EMPLOYEE CLASS USING AHP AND TOPSIS METHODS AT PT. TELKOM - Ega Shela Marsiani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
The Decision Support System (SPK) developed in this study aims to assist the management of PT. Telkom in determining the increase in the Customer Service Representative (CSR) employee class based on a number of relevant criteria. The AHP and TOPSIS methods are used as a basis for decision making. First, the AHP method is used to obtain the relative weight of each considered criterion. These criteria may include things such as work performance, knowledge and skills, work experience, and other factors deemed important in evaluating CSR employees. By using AHP, the relative weight of each criterion can be determined based on the relative preferences of PT management. Telkom. After that, the TOPSIS method was used to rank CSR employees based on their suitability scores with the ideal solution. The ideal solution in this context is the most deserving CSR employee to get a promotion. TOPSIS compares each CSR employee with positive ideal solutions (employees with the best criteria) and negative ideal solutions (employees with the worst criteria). Using mathematical calculations, TOPSIS assigns a score to each CSR employee and generates a rating indicating their degree of suitability with the ideal solution. In practice, this decision support system will enable the management of PT. Telkom to input CSR employee data, determine the criteria weight using the AHP method, and obtain employee ratings based on the TOPSIS method. This information can be used as a basis for making decisions that are more objective and accurate in determining the increase in the class of CSR employees. By using a combination of AHP and TOPSIS methods, this decision support system is expected to help PT. Telkom is in the process of making decisions that are more efficient and reliable in determining the increase in the class of CSR employees.